REGISTER PENGASUHAN BAYI DI KEC. BANYUMANIK KOTA SEMARANG DAN DI KEC. ROWOSARI KAB. KENDAL: TELAAH ETNOLINGUISTIKREGISTER PENGASUHAN BAYI DI KEC. BANYUMANIK KOTA SEMARANG DAN DI KEC. ROWOSARI KAB. KENDAL: TELAAH ETNOLINGUISTIK - Baehaqie, Imam (Lingua, 2010)
There is a slight different in the language use of baby parenting in Semarang Municipality and Kendal Regency.In this research the forms of baby parenting register in Semarang Municipality and Kendal Regency aredescribed and classified and the cultural background of the baby parenting register use in both second levelregions is outlined as well.The approach of the current study consists of two, namely theoretical and methodological approaches.Theoretically, the approach used in this research is the one of ethnolinguistics. In methodological terms,however, it is qualitative descriptive. The research data takes the form of all baby parenting registers inSemarang Municipality and Kendal Regency. The source of the research data is the utterance of mothersparenting their baby existing in both regions. The data collection is performed using conversation method with abasic technique in the form of captivate technique. Additionally, introspective method is also used. The data isanalyzed using qualitative method. The analyzed data is presented descriptively.From the obtained data, it is found that the baby parenting registers in Semarang Municipality and KendalRegency have quite varied forms. Those forms can be classified on the basis of (1) lingual unit, (2) lexiconsource, (3) need framing, and (4) actor.The cultural background of this baby parenting register use is the situational factor taking the form of thelocal social culture. This social culture can be seen in the form of the tradition developing in the baby parenting,since the age of 1 day, 7/9/11/13 days, selapan (35 days), until 1 year old developed in those two second levelregions.In addition, another issue supporting the formation of the baby parenting register is the difference in point ofview towards an event taken place around the language users in utterance event, between those in SemarangMunicipality and Kendal Regency.From the available conclusion, it is recommended for language researchers and followers of Copenhagenschool, i.e. a school of thought which, in addition to attempting to comprehend a language pattern, try tocomprehend any socio-cultural fields in general (in the context of the language) to perform research on registerin other fields. The policy makers in childhood education field are expected to be able to use it as supplementalinformation in making a policy concerning the early childhood education since seeing the lexicons related to thebaby parenting enables one to discover the working description of baby parenting.Keywords: register, baby parenting, and ethnolinguistics.